Ancillary Benefits of Climate Policy - Anil Markandya; Dirk T.G. Rübbelke (Fondazione Eni Enrico Mattei (FEEM), 2003)
The benefits of climate policy normally consist exclusively of the reduced impacts of climate change, i.e., the policy's primary aim. Our analysis of benefits of climate policy suggests, however, that researchers and policymakers should also take account of ancillary benefits, e.g., in the shape of improved air quality induced by climate protection measures. A consideration of both, primary and ancillary benefits, has a positive influence on global climate protection efforts, e.g., because the regional impact of ancillary effects attenuates easy-riding motives of countries with respect to their provision of climate protection. In this article, we analyze the nature of ancillary benefits, present an overview of European assessment studies and explain possible methods to estimate ancillary benefits. Main differences between primary and ancillary benefits are pointed out. Furthermore, we stress the major influences of ancillary benefits on climate policy. Finally, we present one of the first models integrating primary and ancillary benefits. By this model quantitative results are calculated with respect to ancillary benefits in the UK considering different green-house gas (GHG) control levels. It is observed that the ancillary benefits could cover about 4 percent of the full GHG reduction cost.
Keywords: H41; Q28; 330; Climate Policy; Ancillary Benefits; Pollution Control; Klimaschutz; Luftreinhaltung; Wohlfahrtsanalyse; Großbritannien